Printed Thin Film On Copper And Pcb For Corrosion Application - Ahmad, Nur Hidayah (Universiti Sains Malaysia, 2021)
Corrosion resistance is promptly one of the most critical issues in the electronics sector, especially in Printed Circuit Board (PCB) applications. The solder in electronic connection also experience corrosion as it may expose to the atmosphere, due to the design and mounting of electronic component on a substrate or PCB. Corrosion causes device failures and massive costs, and the real impact of corrosion-caused losses is not widely presented in the industrial sector. As a result, corrosion is now one of the most complicated issues, and it is gaining attention in recent years due to higher product warranties, advanced technologies, and phase changes brought by the recent laws affecting the electronics sector. Furthermore, a delicate and unstudied characteristic of SAC305 thin film solder on copper characteristic was limited. Therefore, this project was conducted to study the corrosion characteristic of SAC305 thin film solder in acidic medium. The corrosion behaviour of as-reflowed SAC305/Cu thin film solder with the temperature of 250℃ at 480 seconds was investigated by using a galvanic corrosion test in a 30% sodium chloride (NaCl) solution. The microstructure, structural phase, and hardness of the intermetallic compounds formed were determined. After solder reflow, the interfacial IMC formed between SAC305, and Cu substrate are Cu6Sn5 and Ag3Sn. The corroded surface was mainly composed of SnO and SnO2 for as-reflowed SAC305/Cu. These results clearly indicate the corrosion characteristics of SAC305 thin film solder in acidic media, as well as prospective guidance for electronic device maintenance to ensure safe operation and extended in-service lifetime.